ANALISIS MOTIVASI KERJA PEGAWAI PADA DINAS KEBUDAYAAN DAN PARIWISATA KOTA PEKANBARU - Sri Rahmi Putri; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study aims to determine the motivate of pekan baru culture andtourism department staff and also to determine the dominant factor whichaffecting their motivation.This study using descritive qualitatve method to examine the issues raised.This study took sample as much as 40 peoples. Medium use to collect data wereobservation, interview, questionnaire. Interval were determine by using likertscale.According to the result of this study, staff motivation in pekanbaru cultureand tourism department were high. The most dominat factor that afffecting theirmotivation are the maintaining factor (extrinsic) namely compensation. Accordingto respondents feedback, provision an appropriate compensation that predefinedby the organizations will give great affect towards to staff motivation inpekanbaru culture & tourism department, and vice versa.Keywords : human resources, peformance, work motivation.